Repeatable Collaboration Processes for Mature Organizational Policy Making - Nabukenya, Josephine; Bommel, Patrick van; Proper, H.A. Erik (Springer, Berlin, Heidelberg., 2008)
Organizational policy making processes are complex processes in which many people are involved. Very often the results of these processes are not what the different stakeholders intended. Since policies play a major role in key decision making concerning the future of organizations, our research aims at improving the policies on the basis of collaboration.In order to achieve this goal, we apply the practice of collaboration engineering to the field of organizational policy making. We use the thinklet as a basic building block for facilitating intervention to create a repeatable pattern of collaboration among people working together towards achieving a goal. Our case studies show that policy making processes do need collaboration support indeed and that the resulting policies can be expected to improve.
Keywords: Policy Process, Policy Objective, Collaborative Process, Organizational Policy, Policy Making Process